A survey of semantic applications in communications - Yingzi XU; Yuan LIU; Mengran SHI; Shujun HAN; Chen DONG; Bizhu WANG (Dianxin kexue)
With the development of artificial intelligence technology and wireless communication technology, the future communication networks for all things intelligent connected uses semantic segmentation, semantic network and other technologies more and more frequently, and the semantic information-based technologies are applied to various fields.Semantic communication is a communication method for multi-agent interaction.By extracting the requirements and information characteristics of agents, coding and transmission, the accurate transmission of semantics from agents can be realized.Firstly, the development of semantic related technology in artificial intelligence was analyzed.And then the application of semantics in communication was summarized.Finally, the application of semantic information in other fields was analyzed, and the development trend of semantics in other fields was discussed.